ADMISSIBILITY IN _n^0-ENUMERATIONS - Soskova, Alexandra; Soskov, Ivan (Ann. Sofia Univ. Fac. Math. and Inf., 1998)
In the paper we introduce the notion of _n^0 partial enumeration of an abstract structure A. Given a k ≤ n, we obtain a characterization of the subsets of A possessing _k^0 pullbacks in all _n^0 partial enumerations of A.